2014
DOI: 10.1016/j.cub.2014.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Anillin Regulates Cell-Cell Junction Integrity by Organizing Junctional Accumulation of Rho-GTP and Actomyosin

Abstract: Summary Anillin is a scaffolding protein that organizes and stabilizes actomyosin contractile rings and was previously thought to function primarily in cytokinesis [1–10]. Using Xenopus laevis embryos as a model system to examine Anillin’s role in the intact vertebrate epithelium, we find that a population of Anillin surprisingly localizes to epithelial cell-cell junctions throughout the cell cycle, whereas it was previously thought to be nuclear during interphase [5, 11]. Further, we show that Anillin plays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
158
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(168 citation statements)
references
References 38 publications
9
158
1
Order By: Relevance
“…This abnormal accumulation of the key contractile ring components, F-actin and Myosin II, is likely to drive the cytokinesis defects observed when the Mgc SxIP motif is mutated. This is consistent with previous reports demonstrating cytokinesis failure due to an over-robust RhoA activity zone and/or actomyosin contractile ring ( DeWard and Alberts, 2009;Manukyan et al, 2015;Miller and Bement, 2009;Reyes et al, 2014). Collectively, these data provide in vivo evidence that the Mgc SxIP motif plays a functional role in regulating cytokinesis by mediating the precise localization of Centralspindlin in order for proper localized RhoA activation and accumulation of downstream targets.…”
Section: Mutation Of the Mgcracgap Sxip Motif Disrupts Equatorial Accsupporting
confidence: 81%
“…This abnormal accumulation of the key contractile ring components, F-actin and Myosin II, is likely to drive the cytokinesis defects observed when the Mgc SxIP motif is mutated. This is consistent with previous reports demonstrating cytokinesis failure due to an over-robust RhoA activity zone and/or actomyosin contractile ring ( DeWard and Alberts, 2009;Manukyan et al, 2015;Miller and Bement, 2009;Reyes et al, 2014). Collectively, these data provide in vivo evidence that the Mgc SxIP motif plays a functional role in regulating cytokinesis by mediating the precise localization of Centralspindlin in order for proper localized RhoA activation and accumulation of downstream targets.…”
Section: Mutation Of the Mgcracgap Sxip Motif Disrupts Equatorial Accsupporting
confidence: 81%
“…Given the requirement for Fmn1 in apical emergence (Sedzinski et al, 2016), we probed the role of RhoA in this process. We first measured the dynamics of RhoA activity using the active RhoA biosensor (rGBD), which has been shown previously to be effective in Xenopus (for examples, see Benink and Bement, 2005;Breznau et al, 2015;Reyes et al, 2014). We expressed GFP-rGBD in the mucociliary epithelium and found that throughout the expansion phase of the MCC apical surface, the fluorescence intensity of normalized active RhoA increased (Fig.…”
Section: Rhoa Controls the Dynamics Of MCC Apical Emergencementioning
confidence: 99%
“…Upon depletion of anillin, pulses of RhoA activation at discrete spots at junctions of Xenopus cells occur with higher frequency, but reduced life-time [90]. Such altered oscillation of active RhoA severely impairs adherens junctions [54,90]. The direct binding of anillin with active RhoA [89] may be a mechanism to maintain spatial and temporal regulation, albeit this has not yet been formally shown.…”
Section: Different Hues Of the Same Colourmentioning
confidence: 99%
“…Anillin, a bundling protein, interacts with and recruits RhoA to the cytokinesis furrow and cell-cell contacts, where it controls active RhoA localization [89,90]. Upon depletion of anillin, pulses of RhoA activation at discrete spots at junctions of Xenopus cells occur with higher frequency, but reduced life-time [90]. Such altered oscillation of active RhoA severely impairs adherens junctions [54,90].…”
Section: Different Hues Of the Same Colourmentioning
confidence: 99%